Narrative therapy : an introduction for counsellors - Payne, Martin (SAGE Publications, 2006)
Drawing on the ideas of Michael White and David Epston, this fully revised, extended and updated Second Edition incorporates the progression of their thinking over the past five years and introduces developments initiated by other narrative therapists worldwide. New material has been added around counseling for post-traumatic reactions, couples conflict and a sense of personal failure.